Design and Testing of a Multi-port Sustainable DC Fast-charging System for Electric Vehicles. Issue 14 (26th August 2016) - Lu, Xiaomin; Iyer, K. Lakshmi Varaha; Lai, Chunyan; Mukherjee, Kaushik; Kar, Narayan C.
Abstract: In this era of electrified transportation, inadequate fast-charging infrastructure and limited driving ranges in vehicles due to current energy storage technology remain bottlenecks in motivating consumers to rapidly shift to these electrified vehicles. Mass integration of these vehicles into the grid in the future would result in huge stress on the existing grid in terms of quantity and quality of power consumed. Understanding these issues in detail, this article exclusively discusses the design, development, and comprehensive testing of a multi-port sustainable fast-charging station involving solar photovoltaic, an in-house battery electric vehicle, the utility grid, multiple power electronic converters, and proper control under various modes of operation of the charging station. Such a charging station would enable quick and conventional charging with a lower power level through sustainable power, if available, hence reducing the impact on the grid and the energy cost of system operation.